RAD51 protein is a predictor of chemosensitivity and survival prognosis in patients with advanced high-grade serous ovarian cancer undergoing neoadjuvant chemotherapy - Liu, Hui; Xia, Yufang; Chen, Yunqing; Qi, Huiyang; Ji, Huixiang; Ji, Shujun; Lou, Yanhui (Frontiers in Oncology, 2025)
ObjectiveThe primary aim of this study is to investigate the relationship between the expression of the homologous recombination protein RAD51 and the CA125 elimination rate constant K (KELIM) score in the context of sensitivity to neoadjuvant chemotherapy (NACT) in patients with advanced high-grade serous ovarian cancer. Additionally, we explore the potential of RAD51 expression and the KELIM score as biomarkers of chemotherapy sensitivity.MethodsWe selected a cohort of 43 patients with advanced high-grade ovarian carcinoma who underwent intermediate tumor cytoreductive surgery (IDS) following NACT between January 2017 and December 2019. Pathological tissue samples were collected from pre-chemotherapy and post-IDS ovarian cancer tissues, as well as from normal ovarian tissues of 12 control subjects. Immunohistochemistry was used to evaluate RAD51 protein expression. Concurrently, the KELIM score was calculated for NACT patients. Progression-free survival (PFS) and overall survival (OS) were monitored, and the correlation between RAD51 expression, chemotherapy sensitivity, and survival outcomes was assessed. Furthermore, we analyzed the combined prognostic value of RAD51 expression and the KELIM score in predicting NACT sensitivity and prognosis in advanced high-grade serous ovarian cancer.ResultsThe expression rate of RAD51 protein in ovarian cancer tissues was significantly higher compared to normal ovarian tissues (95.3%VS 16.7%, P < 0.05). High RAD51 expression was significantly negatively correlated with the KELIM score and NACT sensitivity. Both RAD51 expression and the KELIM score were associated with the recurrence of platinum resistance after surgery. Patients with high RAD51 expression exhibited a higher recurrence rate of platinum resistance compared to those with low RAD51 expression. Similarly, patients with a KELIM score < 1 had a statistically significantly higher recurrence rate of platinum resistance than those with a KELIM score ≥ 1 (P < 0.001). There was no significant statistical difference between the AUC of RAD51 expression for predicting platinum-resistant recurrence and that of the KELIM score (P> 0.05). The AUC of the combination of RAD51 expression and the KELIM score showed an increasing trend compared with the KELIM score and RAD51 expression respectively, yet there was no statistical difference among the three. High RAD51 expression was associated with lower PFS and OS, indicating a poorer survival prognosis.ConclusionRAD51 protein expression is closely related to the sensitivity of neoadjuvant chemotherapy in advanced high-grade serous ovarian cancer. RAD51 protein expression offers a valuable tool for predicting chemotherapy sensitivity, platinum resistance recurrence, and survival outcomes in patients with advanced epithelial ovarian cancer.